Language - Related Revisions in Published Articles Written by Non-native PhD Students in Applied Linguistics Discipline - Jalil Abdi; Mohammad Azizi (International Journal of Practical and Pedagogical Issues in English Education)
One of the most important accomplishments for academics is to publish their research outputs in accredited journals. Journal editors and reviewers often call for an extensive range of modifications before granting acceptance. The present study delved into the type and rate of these revisions on the manuscripts submitted to highly indexed ELT journals by Iranian PhD students in applied linguistics. It explored the proportion and focus of language-related revisions in terms of grammar, lexis, and discourse. To this end, 24 published research papers written by Iranian PhD students along with their first draft manuscripts were selected, and their introductions, results, and discussions were analyzed and cross-checked to identify language-related modifications. The results showed that the most frequent type of modifications required by journal editors and reviewers were discoursal followed by grammatical and lexical revisions. The lexical revisions required were all unwarranted. The findings can help young researchers in applied linguistics to preemptively minimize the need for language-based revisions in their academic writings through addressing the identified problematic areas in their manuscripts.